PO.2.45 Autoantibodies associated with systemic sclerosis (SSC) in three diseases characterized by type I interferons: a comparison between SLE, primary Sjögren's syndrome, SSC and healthy blood donors. (27th September 2022) - Andraos, R; Ahmad, A; Eriksson, P; Dahlström, Ö; Wirestam, L; Dahle, C; Hesselstrand, R; Andréasson, K; Sjöwall, C
Abstract : Purpose: SLE, primary Sjögren's syndrome (pSS) and systemic sclerosis (SSc) are heterogeneous autoimmune diseases with a dysregulated type I interferon (IFN) system. The diseases primarily affect females and often show overlapping clinical findings, e.g., arthritis and Raynaud's phenomenon (RP), which may result in diagnostic challenges. The Systemic Sclerosis Profile is an immunoblot test, including different autoantibodies (aab), which has been launched to aid the identification of patients with recent-onset SSc and to stratify patients into more homogenous subsets. Herein, we investigated whether SSc-associated aab also could be found in patients with well-characterized SLE and pSS, and whether these aab correlate to clinical phenotypes. In addition, we employed samples with clinical data from patients with SSc as well as from healthy blood donors (HBD). Methods: Serum samples from SLE (n=282), pSS (n=116), SSc (n=57) and HBD (n=236) were analyzed using a commercially available immunoassay (Systemic Sclerosis Profile EuroLine [IgG]; Euroimmun AG, Lübeck, Germany). IFN-alpha was quantified in the sera using ELISA (Mabtech AB, Nacka, Sweden). Data on clinical manifestations of patients as well as self-reported information on RP of HBD were available. Results: Significantly higher proportion of subjects with SSc than SLE, pSS and HBD had aab against Scl-70, CENP-A, CENP-B, RNA polymerase-III 11kDa, RNA polymerase-III 155kDa, PM-Scl100, PM-Scl75 and Ku ( Figure 1 ). No significant difference in prevalence was seen regarding aab against fibrillarin, NOR90, Th/To or PDGFR. Anti-Ro52/SSA was found in a higher proportion of patients with pSS (80.2%) and SLE (41.1%) than in SSc (22.8%). Among patients with SLE, anti-NOR90 was associated with discoid lupus (p=0.025) whereas anti-CENP-A was inversely associated with hematological disorder (p=0.005) and photosensitivity (p=0.024). Anti-CENP-A was inversely associated with mucocutaneous (ACR criteria 1–4, merged) involvement (p=0.014). Anti-CENP-B was significantly associated with serositis (p=0.005), anti-Ku with lupus nephritis (p=0.007) and anti-Ro52/SSA with neurological disorder (p=0.021). Among patients with SSc, 50/57 (87.7%) tested positive for ≥1 specificity and 6 of the 7 (85.7%) immunoblot negative patients were ANA positive with immunofluorescence microscopy. Pulmonary fibrosis was associated with anti-Scl-70 (p=0.008), anti-RNA polymerase-III 11kDa (p=0.003) and anti-RNA polymerase-III 155kDa (p=0.003). Pulmonary arterial hypertension was associated with anti-CENP-A (p=0.05). Among HBD, aab against RNA polymerase-III 155kDa (p=0.027) and PM-Scl100 (p=0.018) were associated with RP. Conclusions: We demonstrate that the 13 aab included in the Systemic Sclerosis Profile immunoassay are commonly detected among patients with SSc, but they are also frequent among individuals with other diseases characterized by type I IFNs. This information is important to convey to clinicians, especially as patients may present with similar manifestations or overlap syndromes. In SLE, we observed associations between clinical manifestations and SSc-associated aab which have not previously been reported.